Una visión criminológica de la percepción de seguridad en “Barrio Antiguo” centro de Monterrey, Nuevo León - Arriaga Avalos, Leonardo David (Archivos de criminología, seguridad privada y criminalística, 2023)
The purpose of this research work is to carry out a study of the perception of security and the use of some tools that criminologists can use to identify the consequences of crime, especially by applying some data visualization techniques such as thematic maps, a technique that helps to identify and georeferenced the structural problems of a geographic space by means of exploratory security walks. In addition, the use of perception and victimization surveys provides valuable information that reduces unreported crimes. Criminology can make use of different disciplines and tools (mentioned above) that allow it to make an interpretation of the causes and effects of crime.